THE ARTIFICIAL URINARY SPHINCTER FOR THE TREATMENT OF URINARY INCONTINENCE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The artificial urinary sphincter (AUS) imposed itself as the most effective treatment for urinary incontinence after surgery of the prostate. Along with the technological development and improvement of the device over time, more indications have emerged, most of which are not yet considered mainstream but provide an alternative in the armamentarium of the modern urologist. The artificial urinary sphincter was first introduced in 1974 and has undergone significant evolution since then, with several manufacturers currently active in this market. This treatment is effective and safe, although some potential complications may still occur and need to be understood and accepted by the patient. Considering that there is no other therapeutic option comparable in terms of efficacy, the artificial urinary sphincter deserves its place as the gold standard treatment for post-prostatectomy incontinence in males. We conclude that the AUS brought significant improvement in the health-related quality of life for most men with incontinence after prostatic surgery; however, there is still a need for further development of the device, as the complication rate remains high, despite a noticeable improvement over the decades.
Keywords: Artificial urinary sphincter; Intrinsic sphincteric deficiency; Urinary incontinence; Post prostatectomy incontinence